2017
DOI: 10.1002/hep.29241
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance elastography measured shear stiffness as a biomarker of fibrosis in pediatric nonalcoholic fatty liver disease

Abstract: Magnetic Resonance Elastography (MRE) is promising for non-invasive assessment of fibrosis, a major determinant of outcome in nonalcoholic fatty liver disease (NAFLD). However, data in children are limited. Study aims were to determine accuracy of MRE for detection of fibrosis and advanced fibrosis in children with NAFLD, and to assess agreement between manual and novel automated reading methods. We performed a prospective, multi-center study of 2D-MRE in children with NAFLD. MR-elastograms were analyzed manua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 35 publications
6
92
4
3
Order By: Relevance
“…Although MR elastography is used in pediatric and young adult patients, the data to support its use in this population are currently limited. Some of the larger, primarily adult, studies have included pediatric and young adult subjects, but to date there have only been two primary pediatric studies (6,7). Those studies showed good diagnostic performance of MR elastography for identification of fibrosis in pediatric patients and support the use of MR elastography.…”
Section: Mr Imaging and Analysismentioning
confidence: 99%
“…Although MR elastography is used in pediatric and young adult patients, the data to support its use in this population are currently limited. Some of the larger, primarily adult, studies have included pediatric and young adult subjects, but to date there have only been two primary pediatric studies (6,7). Those studies showed good diagnostic performance of MR elastography for identification of fibrosis in pediatric patients and support the use of MR elastography.…”
Section: Mr Imaging and Analysismentioning
confidence: 99%
“…17 However, many recent reports rely on a single encoding direction. [18][19][20][21][22][23][24][25][26] For gradient echo sequences, the absence of refocusing pulses makes it necessary to acquire reference phase maps for removing systematic phase errors. This is achieved by acquiring a non-encoded reference scan, 27 by timing the encoding gradients on alternating lobes of the acoustic motion, 28 or by acquiring a second dataset with an opposed motion encoding gradient polarity.…”
Section: Motion Encodingmentioning
confidence: 99%
“…Multiple studies and meta-analyses have shown that MRE has high diagnostic performance for diagnosing advanced fibrosis in NAFLD with AUROCs > 0.90 24,26,101,102,104,[143][144][145][146] (see Table 4 on salient MRE findings in NAFLD populations). The diagnostic performance of MRE for diagnosing advanced fibrosis in NAFLD is higher than that of ultrasound elastography and serum biomarkers.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…While MRE has somewhat comparable accuracy to ultrasound-based elastography, it has some significant drawbacks such as cost and increased test time. 52 And though it’s becoming more widely available, MRE is still performed only at specialized centers, which limits accessibility to relatively few f patients.…”
Section: Discussionmentioning
confidence: 99%